Knowledge and Attitudes About Attention-Deficit/Hyperactivity Disorder and Specific Learning Disorder in an Urban Indian Population. Issue 6 (June 2016) - Mukherjee, Sayantani; Shah, Henal R.; Ramanathan, Seethalakshmi; Dewan, Mantosh
Abstract : Abstract: Attention-deficit/hyperactivity disorder (ADHD) and specific learning disorders (SLDs) are an important cause of scholastic backwardness among children and often go unrecognized. Few studies have examined knowledge and attitudes toward ADHD and SLD among school-aged children. To address this deficit, 120 school-aged children, attending a child guidance clinic in Mumbai, were interviewed using a questionnaire that examined children's knowledge and attitudes about ADHD and SLD. The results were compared both qualitatively and quantitatively with a frequently occurring medical illness, common cold. Approximately 80% to 100% of children were aware of their illness; however, a large variation was noted in the proportion of children (15%–80%) who could describe their symptoms, provide accurate attributions for their illness, and identify treatment modalities. Children with ADHD reported greater control over their illness. The study identified a significant lack of knowledge about ADHD and SLD among school-aged children in India and discusses implications of this finding.